2022
DOI: 10.3390/biomedicines10020503
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effect of Idebenone through Modulation of the Intrinsic Mitochondrial Pathway of Apoptosis in Human Retinal Pigment Epithelial Cells Exposed to Oxidative Stress Induced by Hydrogen Peroxide

Abstract: Idebenone is a ubiquinone short-chain synthetic analog with antioxidant properties, which is believed to restore mitochondrial ATP synthesis. As such, idebenone is investigated in numerous clinical trials for diseases of mitochondrial aetiology and it is authorized as a drug for the treatment of Leber’s hereditary optic neuropathy. Mitochondria of retinal pigment epithelium (RPE) are particularly vulnerable to oxidative damage associated with cellular senescence. Therefore, the aim of this study was to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…Figure 3 B shows that neither HG nor DHA under both physiological and HG conditions stimulate the activation of Nrf2 mRNA expression, with values 1.98 ± 1.18 for HG, 1.39 ± 0.72 for DHA, and 1.48 ± 0.71 for HG+DHA respectively. To evaluate the potential transcriptional activation of Nrf2, we both assayed Nrf2 protein expression in whole cells subjected to the different treatments (see Figure S2, Supplementary Materials ) [ 40 ] and evaluated the expression of Nqo1 and HO-1. The normalized expression of HO-1 and NQO1 is reported in Figure 3 C,D, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 B shows that neither HG nor DHA under both physiological and HG conditions stimulate the activation of Nrf2 mRNA expression, with values 1.98 ± 1.18 for HG, 1.39 ± 0.72 for DHA, and 1.48 ± 0.71 for HG+DHA respectively. To evaluate the potential transcriptional activation of Nrf2, we both assayed Nrf2 protein expression in whole cells subjected to the different treatments (see Figure S2, Supplementary Materials ) [ 40 ] and evaluated the expression of Nqo1 and HO-1. The normalized expression of HO-1 and NQO1 is reported in Figure 3 C,D, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, oxidative stress has been suggested as a critical factor in the pathogenesis of various retinal degenerative diseases ( Chan et al, 2020 ; Dammak et al, 2021 ; Clementi et al, 2022 ). Therefore, the application of antioxidants to preserve RPE functional integrity from oxidative damage can be considered as one of the prospective approaches to reduce the pathogenesis of ocular diseases including retinal degeneration ( Léveillard et al, 2019 ; Sadda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Idebenone, a ubiquinone short-chain synthetic analog, is believed to restore mitochondrial ATP synthesis with antioxidant properties [ 241 ]. Punicalagin (2,3-hexahydroxydiphenoyl-gallagyl-D-glucose), a polyphenol extracted from pomegranate (Punica granatum), is a potent antioxidant in several cell types [ 242 ].…”
Section: Therapeutic Strategies For Dmementioning
confidence: 99%
“…Previous studies showed that both idebenone and punicalagin could protected RPE from oxidative damage, suggesting their possible roles in DR and DME treatment. Idebenone protected RPE through modulation of the intrinsic mitochondrial pathway of apoptosis [ 241 ]. Punicalagin exerted its effect to reduce oxidative stress and decrease the apoptosis via enhancing mitochondrial functions [ 242 ].…”
Section: Therapeutic Strategies For Dmementioning
confidence: 99%